Suicide crisis calls to emergency services: Cohort profile and findings from a data linkage study in Queensland, Australia. (February 2022) - Meurk, Carla; Wittenhagen, Lisa; Bosley, Emma; Steele, Megan L; Bunting, Denise; Waterson, Elissa; Edwards, Bronwen; Martain, Ben; Heffernan, Ed
Background and Aims: Police and paramedics play a crucial role in responding to suicide crises in the community. However, little is known about the nature, extent, precipitating factors, pathways and outcomes of a suicide-related call to emergency services and what responses will most effectively and compassionately meet the needs of those in crisis. Partners in Prevention: Understanding and Enhancing First Responses to Suicide Crisis Situations (PiP) was established to address these knowledge gaps. Methods: This article describes (1) the methodology used to construct the PiP dataset, a population-wide linked dataset that investigates the characteristics and health pathways of individuals in Queensland who were the subject of a suicide-related call to police or paramedics; and (2) preliminary findings on service demand, demographics and health services utilisation. Results: We identified 219, 164 suicide-related calls to Queensland Police Service or Queensland Ambulance Service that were made over the 3-year period 1 February 2014 to 31 January 2017. A total of 70, 893 individuals were identifiable via records linkage. The cohort linked to more than 7, 000, 000 health records. We estimated that police or paramedics in Queensland received on average 209 calls per day, with increases year on year over the study period. Analysis of demographic data highlighted the heterogeneous nature of this cohort and important demographic variations between individuals in contact with police versus ambulance services. Discussion: The PiP dataset provides a strong foundation for a multi-modal dataset that can be built on over time, both cross-sectionally and longitudinally. Further linkages to Medicare Benefits Schedule, Pharmaceutical Benefits Scheme and social care datasets are planned. Conclusion: Detailed population-level analysis that data linkage can provide is critical to improving understanding and responses to suicide crisis situations. The PiP study is a world first and provides a unique opportunity to improve responses to this public health problem.